In situ bone regeneration enabled by a biodegradable hybrid double-network hydrogel. (10th June 2019) - Zhang, Yuanhao; Chen, Mingjiao; Tian, Jia; Gu, Ping; Cao, Hongliang; Fan, Xianqun; Zhang, Weian
Abstract : The biodegradable hybrid double-network hydrogel for stem cell-enhanced bone regeneration. Abstract : Stem cell therapy based on advanced biomaterials provides a promising strategy in bone tissue engineering. Nevertheless, guided bone regeneration which fulfills the criteria in terms of biomechanics, biodegradability and bioactivity is highly appealing but challenging. Inspired by the superior double-network (DN) structure, herein, a biodegradable hybrid DN hydrogel is proposed to promote in situ bone regeneration. The DN hydrogel is constructed by interspersing a methacrylated gelatin (GelMA) network into a well-defined nanocomposite (NC) hydrogel consisting of methacrylated chitosan (CSMA) and polyhedral oligomeric silsesquioxane (POSS) via a two-step photo-crosslinking process. The hybrid DN hydrogel has the following advantageous characteristics: (i) it exhibits enhanced stiffness and toughness benefiting from the inorganic POSS units and unique energy dissipation; (ii) naturally occurring biomacromolecules (chitosan and gelatin) as the hydrogel framework result in an appropriate biodegradation behavior, which can be replaced by newly formed tissues; (iii) it preferentially guides mesenchymal stem cells (MSCs) toward osteogenic differentiation in vitro by detecting the elevated levels of enzyme activity and calcium deposition along with the up-regulated osteogenesis-related genes and proteins; and (iv) accelerated in situ bone regeneration is observed after implanting MSC-loaded hydrogels into rat calvarial defects. Therefore, we provide a new insight to develop functional hydrogels for triggering specific cellular responses toward stem cell therapy and bone-related tissue engineering.